2016
DOI: 10.1139/cjm-2015-0561
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-induced secondary necrosis in conidia of Aspergillus fumigatus

Abstract: Aspergillus fumigatus conidia have been linked to severe aspergillosis in immunocompromised patients. Recently, the cytotoxic effect of secondary metabolites from A. fumigatus conidia was reported. In the present work, a methodology used to detect cell death markers in fungal hyphae was adapted to study conidia cell death. Additionally, the mechanism of H 2 O 2 -induced cell death was studied in A. fumigatus conidia for the first time. Data presented in this work reveal that the H 2 O 2 -induced conidial cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…7A ). High concentration of H 2 O 2 can lead to excessive ROS accumulation and thus cell death ( 55 57 ), which might affect laccase production by fungal cells. We also found that an acceptable concentration of H 2 O 2 (5 mM) slightly reduced the abundance of GSH (by 4%), but significantly increased the abundance of GSSG (by 71%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7A ). High concentration of H 2 O 2 can lead to excessive ROS accumulation and thus cell death ( 55 57 ), which might affect laccase production by fungal cells. We also found that an acceptable concentration of H 2 O 2 (5 mM) slightly reduced the abundance of GSH (by 4%), but significantly increased the abundance of GSSG (by 71%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Results of Angelova et al [53] indicate that exposure of fungal spores to H 2 O 2 promoted oxidative stress evidenced by inhibition of spore germination and biomass production. Oliveira et al [54] reported that H 2 O 2 induces conidia cell death in a dose-dependent manner and through a secondary necrosis mechanism.…”
Section: Resultsmentioning
confidence: 99%